Analisis Perilaku Kepedulian Lingkungan Siswa di SMPN 3 Jakarta - Maudy Marselina; Dian Alfia Purwandari; Achmad Nur Hidayaht (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to describe the environmental awareness behavior of students at SMPN 3 Jakarta. The study utilizes a descriptive research method with data collection techniques including questionnaires, interviews, observations, and literature review. Data analysis techniques employed are data reduction, data presentation, conclusion drawing, and verification. Based on the research findings, students' environmental awareness behavior at SMPN 3 Jakarta is measured through eight indicators: environmental care with a percentage of 38% in the low category, reduction of plastic waste with 33% in the moderate category, waste management with 35% in the moderate category, carbon emission reduction with 40% in the high category, energy conservation with 28% in the moderate category, tree planting with 47% in the moderate category, reuse of items with 47% in the moderate category, and protection of flora and fauna with 38% in the moderate category. The results indicate that many students do not show concern for the environment. This can be seen in behaviors such as indiscriminate littering (e.g., under desks or chairs), unauthorized removal of plants or fruits, and lack of participation in school cleanliness programs such as weekly cleaning activities and duty schedules. Reasons cited include students' laziness to clean classrooms and reliance on peers.